2008
DOI: 10.1017/s1478061508017039
|View full text |Cite
|
Sign up to set email alerts
|

The influence of horse gender on eventing competition performance

Abstract: The study undertook comparative analysis of horse gender and eventing performance. Limited previous research has investigated the impact horse gender may have on performance. However, many competitors have a preference for one gender over another (normally geldings). The study sampled five levels of the sport (intro, pre-novice, novice, intermediate and advanced) and investigated dependent variable penalty scores within the dressage, show jumping and cross-country phases; additionally, final penalty score, ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…Calculating an average ‘points per competition’ by collecting the number of competitions attended where the horse could potentially have gained points removes the effect of the length of career. This is particularly relevant, as highlighted by Whitaker et al , 8 in mares and stallions which may end their career early or take breaks for breeding duties. It is also important as age was not controlled for when gathering data for points, so career lengths of horses sampled will vary.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Calculating an average ‘points per competition’ by collecting the number of competitions attended where the horse could potentially have gained points removes the effect of the length of career. This is particularly relevant, as highlighted by Whitaker et al , 8 in mares and stallions which may end their career early or take breaks for breeding duties. It is also important as age was not controlled for when gathering data for points, so career lengths of horses sampled will vary.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing mares and geldings in eventing, Whitaker and others8 found no significant difference between genders for mean phased and final penalty scores, median rank or points. However, they did not have enough stallions within the dataset for comparative statistical analysis.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…In their studies, Whitaker et al (2008) found that stallions and geldings tend to have better results in competition as mares. Gender is dependent on behavior and controllability of horses, for example mares during the cycle can be difficult to manage in competitions (Viklund, 2010).…”
Section: Resultsmentioning
confidence: 99%